Optimal resource allocation in colonoscopy: timing of follow-up colonoscopies in relation to adenoma detection rates - Sint Nicolaas, J.; de Jonge, V.; van Baalen, O.; Kubben, F. J. G. M.; Moolenaar, W.; Stolk, M. F. J.; Kuipers, E. J.; van Leerdam, M. E.; null (Endoscopy, 2013)
Background and study aims: The assessment of indications for follow-up colonoscopy may help to improve the allocation of available endoscopy resources. The aim of this study was to assess the timing of early follow-up colonoscopy and surveillance utilization in relation to adenoma detection rate (ADR) at follow-up.Methods: An assessment of the timing and yield of follow-up colonoscopies was performed in patients with non-inflammatory bowel disease (IBD) in a Dutch multicenter study. The primary outcome was the number of patients with a prior (index) colonoscopy. The necessity for follow-up procedures was assessed using the ADR.Results: Of 4800 consecutive patients undergoing a colonoscopy, 1249 non-IBD patients had undergone an index colonoscopy. Of these, follow-up procedures were performed within 1 year in 27 % (331/1249). Excluding incomplete colonoscopy, incomplete polypectomy, or poor bowel preparation on index, the ADR on early follow-up was 4 % for symptomatic and 26 % for asymptomatic patients. Among the asymptomatic patients with a follow-up colonoscopy at > 1 year (n = 463), an ADR of 23 % (108/463) was found. In 27 % of these patients, the observed surveillance intervals were in accordance with American Gastroenterological Association (AGA) surveillance recommendations; 60 % were classified as over-utilization and 13 % as under-utilization according to the AGA. Optimal utilization follow-up colonoscopies had higher ADRs on follow-up compared with over-utilized procedures (31 % vs. 17 %; P < 0.001).Conclusions: Follow-up colonoscopy in symptomatic patients within a year has limited value in terms of adenoma detection. A considerable proportion of surveillance colonoscopies are performed too early according to current guidelines, resulting in low detection rates. Both aspects can be targeted for optimal usage in endoscopic capacity.